The Effects of Whole-Body Vibration Exercise on Anticipatory Delay of Core Muscles in Patients with Nonspecific Low Back Pain - Yi-Li Zheng; Hao-Yu Hu; Xiao-Chen Liu; Xuan Su; Pei-Jie Chen; Xue-Qiang Wang (Pain Research and Management)
Objective. The objective of this study is to determine the effect of whole-body vibration (WBV) exercise on the anticipatory delay of core muscles in nonspecific low back pain (NSLBP) patients. Methods. Forty participants with NSLBP were randomly divided into the WBV group and the control group. The sEMG signals of deltoid, erector spines (ES), multifidus (MF), rectus abdominis (RA), and transversus abdominus/internal oblique muscles (TrA/IO) were recorded before and after the intervention in the weight-shifting task. The relative activation time of each muscle was calculated. Results. In the WBV group, the relative activation time of bilateral MF and bilateral TrA/IO was significantly reduced on shoulder flexion (right MF: P=0.014; left MF: P=0.011; right TrA/IO: P=0.008; left TrA/IO: P=0.026). As for shoulder abduction, except for the left TrA/IO and the left RA, the relative activation time of other muscles was significantly reduced (right ES: P=0.001; left ES: P<0.001; right MF: P=0.001; left MF: P=0.009; right TrA/IO: P<0.001; right RA: P=0.001). In the control group, there was no significant difference in the relative activation time of each muscle before and after the intervention (P>0.05). Conclusions. WBV exercise can effectively alleviate the anticipatory delay of core muscles in NSLBP patients, but the long-term effects still need further study. This trial is registered with ChiCTR-TRC-13003708.